Understanding the microbial components of periodontal diseases and periodontal treatment-induced microbiological shifts. Issue 1 (9th January 2021) - Fragkioudakis, Ioannis; Riggio, Marcello P.; Apatzidou, Danae Anastasia
Abstract : In the mid-1960s the microbial aetiology of periodontal diseases was introduced based on classical experimental gingivitis studies . Since then, numerous studies have addressed the fundamental role that oral microbiota plays in the initiation and progression of periodontal diseases. Recent advances in laboratory identification techniques have contributed to a better understanding of the complexity of the oral microbiome in both health and disease. Modern culture-independent methods such as human oral microbial identification microarray and next-generation sequencing have been used to identify a wide variety of microbial taxa residing in the gingival sulcus and the periodontal pocket. The first theory of the 'non-specific plaque' hypothesis gave rise to the 'ecological plaque' hypothesis and more recently to the 'polymicrobial synergy and dysbiosis hypothesis'. Periodontitis is now considered to be a multimicrobial inflammatory disease in which the various bacterial species within the dental biofilm are in a dysbiotic state and this imbalance favours the establishment of chronic inflammatory conditions and ultimately the destruction of tooth-supporting tissues. Apart from the known putative periodontal pathogens, the whole biofilm community is now considered to play a role in the establishment of inflammation and the initiation and progression of periodontitis in a susceptible host. Treatment is unlikely to eliminate putative pathogens but, when it is thoroughly performed it has the potential to establish a healthy ecosystem by altering the microbial community in numbers and composition and also contribute to the maturation of the host immune response.